Respuesta :

Answer:

[tex]g^2-4g-21=(g-7)(g+3)[/tex]

Step-by-step explanation:

To complete the left side of the equation, we need to bring it to the form

[tex](g-a)(g+b)[/tex]

expanding this expression we get:

[tex]g^2+bg-ag-ab[/tex]

[tex]g^2+(b-a)g-ab[/tex]

Thus we have

[tex]g^2-4g-21=g^2+(b-a)g-ab[/tex]

from here we see that for both sides of the equation to be equal, it must be that

[tex]b-a=-4[/tex]

[tex]-ab=-21[/tex].

Getting rid of the negative signs we get:

[tex]a-b=4[/tex]

[tex]ab=21[/tex]

At this point we can either guess the solution to this system (that's how you usually solve these types of problems) or solve for [tex]a[/tex] and [tex]b[/tex] systematically.

The solutions to this set are [tex]a=7[/tex] and [tex]b=3[/tex]. (you have to guess on this—it's easier)

Therefore, we have

[tex](g-a)(g+b)=(g-7)(g+3)[/tex]

which completes our equation

[tex]\boxed{ g^2-4g-21=(g-7)(g+3)}[/tex]

Answer:

7    3

Step-by-step explanation: